Respuesta :
The given above is an arithmetic sequence with first term equal to 3 and the common difference equal to 4. That is from 7 - 3 = 11 - 7 = 15 - 11. The nth term of an arithmetic sequence is given by the equation,
an = a1 + (n - 1) x d
Substituting the given,
an = 3 + 4(n - 1)
thus, the answer is the fourth choice.
an = a1 + (n - 1) x d
Substituting the given,
an = 3 + 4(n - 1)
thus, the answer is the fourth choice.
Answer: [tex]f(n)=3+4(n-1)[/tex]
Step-by-step explanation:
The given arithmetic sequence : 3, 7, 11, 15...
Here , the first term = [tex]a_1=3[/tex]
Common difference =[tex]d=a_2-a_1=7-3=4[/tex]
We know that function represents any Arithmetic sequence is given by :-
[tex]f(n)=a_1+(n-1)d[/tex] , where n= Number of term= 1,2,3,4....
[tex]a_1[/tex] is the first term.
d= common difference.
For the given sequence , the function would be :-
[tex]f(n)=3+4(n-1)[/tex]
Hence, the function represents the given arithmetic sequence :
[tex]f(n)=3+4(n-1)[/tex]